A tonal split in bound argument pronouns in Il-keeknyokie Maa - Kent Rasmussen (LibraryPress@UF, 2001)
This paper describes and accounts for the tonal split between bound argument prefixes of Il-Keekonyokie Maa verbs with (apparently) High and Low tone. Data with the tonal split are given, followed by an analysis showing that the apparent High tone must be lexically unspecified for these prefixes. This analysis is required because a lexical High prefix tone in certain verbs would cause downstep, where down step is not observed. Neutralization of the tone split is then considered, with the data presented and accounted for by an analysis for each of the two verb root classes. The conclusion discusses the need for the apparent word initial High tone to be spread from the stem tone.